Molecular basis for the differential sensitivity of rat and human α9α10 nAChRs to α-conotoxin RgIA - Azam, Layla (2012)
The α9α10 nicotinic acetylcholine receptor (nAChR) may be a potential target in pathophysiology of the auditory system, chronic pain and breast and lung cancers. Alpha-conotoxins, from the predatory marine snail Conus, are potent nicotinic antagonists, some of which are selective for the α9α10 nAChR. Here we report a two-order of magnitude species difference in the potency of α-conotoxin RgIA for the rat vs. human α9α10 nAChR. We investigated the molecular mechanism of this difference. Heterologous expression of the rat α9 with the human α10 subunit in Xenopus oocytes resulted in a receptor that was blocked by RgIA with potency similar to that of the rat α9α10 nAChR. Conversely, expression of the human α9 with that of the rat α10 subunit resulted in a receptor that was blocked by RgIA with potency approaching that of the human α9α10 receptor. Systematic substitution of residues found in the human α9 subunit into the homologous position in the rat α9 subunit revealed that a single point mutation, Thr56 to Ile56, primarily accounts for this species difference. Remarkably, although the α9 nAChR subunit has previously been reported to provide the principal (+) binding face for binding of RgIA, Thr56 is located in the (−) complementary binding face.